Understanding the vital role of green infrastructure in stormwater management for hydrological control in Penang / Nur Adibah Shalehudin and Ruwaidah Borhan - Shalehudin, Nur Adibah; Borhan, Ruwaidah (2024)
Cities may greatly reduce water runoff volume by implementing features like vegetated swales, rain gardens, permeable pavements, and green roofs. This allows water to be absorbed and stored instead of overwhelming drainage systems. According to JPS Pulau Pinang, more than 50 areas in Pulau Pinang were hit by floods after heavy rain with water levels ranging from 0.1 meters to 0.4 meters. GeorgeTown is one of the locations involved in flooding. Thus, this paper aims to understand green infrastructure in stormwater management and residents' adaptability in GeorgeTown, Pulau Pinang. Green infrastructure is a vital component of sustainable urban and regional planning. Through the integration of natural systems into urban environments, the negative effects of heavy rainfall and urbanization are lessened. Qualitative data collection will be conducted for this research. The study contributes to the understanding of the relationship between green infrastructure, flash flood and community adaptability. Result of this study can prove that green infrastructure is needed in every aspect of hydrological control in terms of improving stormwater management in rapid growth of urbanization. However, it can be one of the supporting needs to educate the stakeholders about the importance of green infrastructure in Georgetown to face the crisis of environmental issues.